Postawy wobec Stanów Zjednoczonych: raport z międzynarodowych badań porównawczych - Stępińska, Agnieszka; Hordecki, Bartosz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The paper presents the results of surveys conducted among students in nearly thirty countries. The surveys concerned the students’ attitudes to the presidential elections in the USA in 2008, and their opinions on the candidates running for election. The attitudes towards the United States, its policy and culture were also surveyed. The results indicate that the attitudes of Polish respondents differ significantly from those of the respondents in other countries. In the fall of 2008, Polish respondents were relatively friendly towards Americans, appreciating their honesty, but disrespecting their incompetence and lack of knowledge. The Polish respondents’ assessments of American policy and culture, the US government and its operations in the international arena were also relatively mild. However, the results of Polish surveys were less favorable to US citizens than the results of earlier surveys. They confirmed that, during the George W. Bush presidency, the attitude of Polish society to everything American slowly, but consistently, grew colder. It seems reasonable to suggest this was a reaction to the US’s global policies and a result of Poles’ dissatisfaction with Polish-American bilateral relations.